Perencanaan dan Perancangan Pusat Kebudayaan Pencak Silat Sebagai Tujuan Wisata Guna Membangun City Branding di Kota Madiun. Tema : Arsitektur Simbolis - Noviani, Risa Tri; Andarini, Risma; Suprobo, F.Priyo (Universitas Widya Kartika Surabaya, 2024)
The planning and design of the Pencak Silat cultural center in Madiun City, with a symbolic architectural approach, are motivated by the absence of a dedicated center for Pencak Silat culture in Madiun City. The Pencak Silat Cultural Center is intended not only as an educational and tourism facility but also as an icon that strengthens the city branding of Madiun in the eyes of domestic and international tourists. To address this challenge, the design method by Charles Jencks is used to ensure an effectively directed design flow. Data collection is conducted quantitatively, including measurements of area and dimensions, and qualitatively, including studying behavioral, socio-cultural conditions, and spatial needs. The selected location for the planning and design is on Taman Praja Street, Madiun City, East Java, Indonesia. The data analysis results provide a synthesis in the form of macro and micro concepts with a symbolic architectural approach. The analysis results recommend the use of the macro concept of Pencak Silat cultural locality. The micro concept of form is linked to Pencak Silat movements, such as the 'sikap pasang' (posture) and 'sikap kuda-kuda' (horse stance). The micro concept of space uses a radial or dispersed spatial arrangement to create a sense of spaciousness and openness. The micro concept of arrangement with the 'kuda-kuda' movement results in a mass arrangement that aligns with the meaning of the 'kuda-kuda' movement.